Divergent Adaptive Strategies by Two Co-occurring Epiphytic Orchids to Water Stress: Escape or Avoidance? - Zhang, Wei (Front Plant Sci, 2016)
Due to the fluctuating water availability in the arboreal habitat, epiphytic plants are considered vulnerable to climate change and anthropogenic disturbances. Although co-occurring taxa have been observed divergent adaptive performances in response to drought, the underlying physiological and morphological mechanisms by which epiphyte species cope with water stress remain poorly understood. In the present study, two co-occurring epiphytic orchids with different phenologies were selected to investigate their drought-resistance performances. We compared their functional traits, and monitored their physiological performances in a 25-days of drought treatment. In contrast to the deciduous species Pleione albiflora, the evergreen species Coelogyne corymbosa had different root anatomical structures and higher values for saturated water content of pseudobulbs. Moreover, plants of C. corymbosa had thicker leaves and epidermis, denser veins and stomata, and higher values for leaf mass per unit area and the time required to dry saturated leaves to 70% relative water content. However, samples from that species had lower values for net photosynthetic rate (A(n)), stomatal length and chlorophyll content per unit dry mass. Nevertheless, due to greater capacity for water storage and conservation, C. corymbosa maintained higher A(n), stomatal conductance (g(s)), and instantaneous water-use efficiency during severe drought period, and their values for leaf water potential were higher after the water stress treatment. By Day 10 after irrigation was restarted, only C. corymbosa plants recovered their values for A(n) and g(s) to levels close to those calculated prior to the imposition of water stress. Our results suggest that the different performance responding to drought and re-watering in two co-occurring epiphytic orchids is related to water-related traits and these two species have divergent adaptive mechanisms. Overall, C. corymbosa demonstrates drought avoidance by enhancing water uptake and storage, and by reducing water losses while P. albiflora employs a drought escape strategy by fixing more carbon during growing season and shedding leaves and roots at dry season, leaving a dormant pseudobulb to minimize transpiration. These findings may improve our understanding of the potential effects that climate change can have on the population dynamics of different epiphytic taxa.